Exceptional energy harvesting from coupled bound states - Felix Kronowetter; Anton Melnikov; Marcus Maeder; Tao Yang; Yan Kei Chiang; Sebastian Oberst; David A. Powell; Steffen Marburg (Nature Communications)
Abstract Sustainable and affordable energy is one of the most critical issues facing society. Noise is ubiquitous, albeit with a low energy density, making it an almost perfect energy source. Bound states in the continuum overcome this problem through a highly localized energy increase. Here, we present theoretical, numerical, and experimental studies on bound state acoustic harvesters. Under white noise excitation, the bound state harvester outperforms the conventional Helmholtz resonator harvester by a factor of 2.2 in terms of amplitude spectral density of the output voltage and by a factor of 10 in terms of output power. A super-bound state is formed by using pressure coupling in a pseudo-free field environment, further increasing the energy enhancement. This results in a 50-fold increase in output voltage compared to a single bound state harvester. Our findings advance the state-of-the-art in sustainable energy harvesting for low-power devices.